Exploring Eighth Grade Students' Perceptions of Their Reading Skills through Self-Assessment at MTS Al Madinah Bolo - Arfah Arfah; Khusnul Khatimah; Anisah Anisah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aimed to explore eighth-grade students' perceptions of their reading skills as reflected through self-assessment. Employing a descriptive quantitative research design, the study involved 14 eighth-grade students from a junior high school selected through total sampling. Data were collected using a Reading Self-Assessment Questionnaire consisting of seven indicators: reading engagement, reading comprehension, strategy use, self-monitoring, reading stamina, reading accuracy, and reading pace. Students responded to each item using a three-point scale (Yes, Somewhat, No), and the data were analyzed through frequency counts and percentage calculations. The findings revealed that students held the most positive perceptions of their reading stamina, with 92.9% reporting confidence in sustaining reading for extended periods. Strategy use also received relatively positive responses, with 50% of students indicating that they actively employed reading strategies when encountering difficulties. However, significant challenges were identified in reading accuracy, comprehension, and self-monitoring. A considerable proportion of students (78.6%) reported difficulties in reading words correctly, while 85.7% indicated that they rarely engaged in retelling as a comprehension monitoring strategy. These findings suggest that while students demonstrate willingness to engage in reading activities, they continue to face challenges in higher-order reading processes. The study underscores the importance of integrating self-assessment into reading instruction as a reflective and diagnostic tool, and recommends that teachers provide explicit instruction in comprehension strategies, vocabulary development, and metacognitive practices to support more effective and autonomous reading development at the junior high school level.